Moderasi Beragama di Perguruan Tinggi Islam Surakarta: Analisis Wacana pada Materi Khotbah Jumat - Arif Bowo, Sigit (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2023)
Religious moderation is a national strategic issue that must be continuously guarded. Religious moderation is vital for all levels of society to create harmony in religion and as a nation. This study aims to describe the results of discourse analysis on the form of religious moderation in Friday sermon material at Islamic universities in Surakarta. The data of this research are words, phrases, clauses, sentences, and discourse in Friday sermon materials at universities in Surakarta. Data collection techniques using record, read, and record techniques. The data analysis technique uses the arithmetic technique. The study results show that the form of religious moderation in Friday sermon material at Islamic universities in Surakarta is divided into the scope and indicators of religious moderation. The scope of religious moderation includes moderation among fellow Muslims, moderation between religions, and moderation within the state. Indicators of religious moderation include national commitment, tolerance, non-violence, and radicalism. Based on the study results, it was concluded that Friday sermon material is a strategic and influential medium in increasing understanding of religious moderation. Moderasi beragama merupakan isu strategis nasional yang harus terus dikawal. Moderasi beragama sangat penting bagi seluruh lapisan masyarakat untuk menciptakan kerukunan beragama dan berbangsa. Penelitian ini bertujuan untuk mendeskripsikan bentuk moderasi beragama pada materi khotbah Jumat di perguruan tinggi Islam di Surakarta. Data penelitian ini berupa kata, frasa, klausa, kalimat, dan wacana dalam materi khotbah Jumat di tiga Perguruan Tinggi Islam di Surakarta, yaitu UIN Raden Mas Said Surakarta, Universitas Muhammadiyah Surakarta, dan Universitas Nahdhatul Ulama Surakarta. Teknik pengumpulan data menggunakan teknik rekam, baca, dan catat. Teknik analisis data menggunakan teknik analisis interaktif. Hasil kajian menunjukkan bahwa bentuk moderasi beragama pada materi khotbah Jumat di perguruan tinggi Islam di Surakarta terbagi dalam ruang lingkup dan indikator moderasi beragama. Ruang lingkup moderasi beragama meliputi moderasi antar sesama muslim, moderasi antarumat beragama, dan moderasi dalam bernegara. Sementara itu, indikator moderasi beragama meliputi komitmen kebangsaan, toleransi, antikekerasan dan radikalisme. Berdasarkan hasil kajian, dapat disimpulkan bahwa materi khotbah Jumat merupakan media yang strategis dan berpengaruh dalam penguatan moderasi beragama.